Ptr/CTL0175 Is Required for the Efficient Recovery of Chlamydia trachomatis From Stress Induced by Gamma-Interferon - Panzetta, María E.; Luján, Agustín L.; Bastidas, Robert J.; Damiani, María T.; Valdivia, Raphael H.; Saka, Héctor A. (Frontiers in Microbiology, 2019)
Chlamydia trachomatis is the most common sexually transmitted bacterial pathogen in humans and a frequent cause of asymptomatic, persistent infections leading to serious complications, particularly in young women. Chlamydia displays a unique obligate intracellular lifestyle involving the infectious elementary body and the replicative reticulate body. In the presence of stressors such as gamma-interferon (IFNg) or beta-lactam antibiotics, C. trachomatis undergoes an interruption in its replication cycle and enters a viable but non-cultivable state. Upon removal of the stressors, surviving C. trachomatis resume cell division and developmental transitions. In this report, we describe a genetic screen to identify C. trachomatis mutants with defects in recovery from IFNg- and/or penicillin-induced stress and characterized a chemically-derived C. trachomatis mutant strain that exhibited a significant decrease in recovery from IFNg- but not penicillin-induced stress. Through lateral gene transfer and targeted insertional gene inactivation we identified ptr, encoding a predicted protease, as a gene required for recovery from IFNg-induced stress. A C. trachomatis LGV-L2 ptr-null strain displayed reduced generation of infectious progeny and impaired genome replication upon removal of IFNg. This defect was restored by introducing a wild type copy of ptr on a plasmid, indicating that Ptr is required for a rapid growth upon removal of IFNg. Ptr was expressed throughout the developmental cycle and localized to the inclusion lumen. Overall, our findings indicate that the putative secreted protease Ptr is required for C. trachomatis to specifically recover from IFNg- but not penicillin-induced stress.